Question

(5x+3)^2

298

likes1492 views

Lurline

4.6

102 Answers

Given the expression:

(5x+3)^2

1. Recognize the formula for squaring a binomial:

(a+b)^2 = a^2 + 2ab + b^2

2. Substitute \(a = 5x\) and \(b = 3\) into the formula:

(5x+3)^2 = (5x)^2 + 2 \cdot (5x) \cdot 3 + 3^2

3. Simplify each term:

(5x)^2 = 25x^2

2 \cdot 5x \cdot 3 = 30x

3^2 = 9

4. Combine all the terms:

25x^2 + 30x + 9

The simplified expression is:

25x^2 + 30x + 9

1. Recognize the formula for squaring a binomial:

2. Substitute \(a = 5x\) and \(b = 3\) into the formula:

3. Simplify each term:

4. Combine all the terms:

The simplified expression is:

Frequently asked questions (FAQs)

What is the product of 53 multiplied by 47?

+

What is the value of f(x) if f(x) = 5 for all x in the domain?

+

Find the unknown side length of a triangle with angle A as 42 degrees, side C as 5 units, and angle B as 88 degrees.

+

New questions in Mathematics